VD_FINDINFO Arrêt / 2025 / 240 vom 26. Mai 2025 - VD Tribunal cantonal (2025)
RAPPORT MÉDICAL, AGGRAVATION DE L'ATTEINTE À LA SANTÉ, FORCE PROBANTE | 28 al. 1 LAI, 4 al. 1 LAI, 17 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA